68Ga-PSMA-11 PET/CT-derived metabolic parameters for determination of whole-body tumor burden and treatment response in prostate cancer - Schmidkonz, Christian; Cordes, Michael; Schmidt, Daniela; Bäuerle, Tobias; Goetz, Theresa Ida; Beck, Michael; Prante, Olaf; Uder, Michael; Wullich, Bernd; Goebell, Peter; Kuwert, Torsten; Ritt, Philipp; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2018)
PURPOSE: We aimed at evaluating the role of 68Ga-PSMA-11 PET/CT-derived metabolic parameters for assessment of whole-body tumor burden and its capability to determine therapeutic response in patients with prostate cancer. METHODS: A total of 142 patients with biochemical recurrence of prostate cancer underwent PET/CT with [68Ga]Ga-PSMA-HBED-CC (68Ga-PSMA-11). Quantitative assessment of all 641 68Ga-PSMA-11-positive lesions in the field of view was performed to calculate PSMA-derived parameters, including whole-body PSMA tumor volume (PSMA-TV) and whole-body total lesion PSMA (TL-PSMA), as well as the established SUVmax and SUVmean values. All PET-derived parameters were tested for correlation with serum PSA levels and for association with Gleason scores. In 23 patients who underwent 68Ga-PSMA-11 PET/CT before and after therapy with either external beam radiation, androgen deprivation, or docetaxel chemotherapy, SUVmax and TL-PSMA were compared to radiographic response assessment of CT images based on RECIST 1.1 criteria and to biochemical response determined by changes of serum PSA levels. RESULTS: PSMA-TV and TL-PSMA demonstrated a significant correlation with serum PSA levels (P < 0.0001) and TL-PSMA was significantly different for different Gleason scores. The agreement rate between TL-PSMA derived from PET and biochemical response was 87% (95% confidence interval, 0.66-0.97; Cohen's κ = 0.78; P < 0.01) and, thus, higher than for SUVmax, which was 74% (95% CI, 0.52-0.90; κ = 0.55; P < 0.01). Furthermore, agreement with PSA was higher for TL-PSMA and SUVmax than for CT-based response evaluation. Discordant findings between PET and CT were most likely due to limitations of CT and RECIST in rating small lymph nodes as metastases, as well as bone involvement, which was sometimes not detectable in CT. CONCLUSION: 68Ga-PSMA-11 PET/CT-derived metabolic tumor parameters showed promising results for evaluation of treatment response. Especially, TL-PSMA demonstrated higher agreement rates with biochemical response compared to SUVmax. Larger, ideally prospective trials are needed to help to reveal the full potential of metabolic parameters derived from PET imaging with 68Ga-PSMA-11.
EVALuna2:34269

99m Tc-MIP-1404-SPECT/CT for the detection of PSMA-positive lesions in 225 patients with biochemical recurrence of prostate cancer - Schmidkonz, Christian; Hollweg, Claudia; Beck, Michael; Reinfelder, Julia; Götz, Theresa; Sanders, James Chester; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Uder, Michael; Wullich, Bernd; Goebell, Peter; et al. (Prostate, 2018)
99m Tc-MIP-1404 (Progenics Pharmaceuticals, Inc., New York, NY) is a novel, SPECT-compatible 99m Tc-labeled PSMA inhibitor for the detection of prostate cancer. We present results of its clinical use in a cohort of 225 men with histologically confirmed prostate cancer referred for workup of biochemical relapse.From April 2013 to April 2017, 99m Tc-MIP1404-scintigraphy was performed in 225 patients for workup of PSA biochemical relapse of prostate cancer. Whole-body planar and SPECT/CT images of the lower abdomen and thorax were obtained 3-4 h p.i. of 710 ± 64 MBq 99m Tc-MIP-1404. Images were visually analyzed for presence and location of abnormal uptake. In addition, quantitative analysis of the SPECT/CT data was carried out on a subset of 125 patients. Follow-up reports of subsequent therapeutic interventions were available for 59% (139) of all patients.Tracer-positive lesions were detected in 77% (174/225) of all patients. Detections occurred at the area of local recurrence in the prostate in 25% of patients (or a total of 56), with metastases in lymph nodes in 47% (105), bone in 27% (60), lung in 5% (12), and other locations in 2% (4) of patients. Detection rates were 90% at PSA levels >=2 ng/mL and 54% below that threshold. Lesional SUVmax values were, on average, 32.2 ± 29.6 (0.8-142.2), and tumor-to-normal ratios 146.6 ± 160.5 (1.9-1482.4). The PSA level correlated significantly with total uptake of MIP-1404 in tumors (P < 0.001). Furthermore, total tumor uptake was significantly higher in patients with Gleason scores >=8 compared to those with Gleason scores <=7 (P < 0.05). In patients with androgen deprivation therapy, the detection rate was significantly higher compared to patients without androgen deprivation therapy (86% vs 71%, P < 0.001). Based on 99m Tc-MIP-1404-imaging and other information, an interdisciplinary tumor board review recommended changes to treatment plans in 74% (104/139) of those patients for whom the necessary documentation was available.SPECT/CT with 99m Tc-labeled MIP-1404 has a high probability in detecting PSMA-positive lesions in patients with elevated PSA. Statistical analysis disclosed significant relationship between quantitative 99m Tc-MIP-1404 uptake, PSA level, and Gleason score.
EVALuna2:13874

Assessment of Treatment Response by 99mTc-MIP-1404 SPECT/CT: A Pilot Study in Patients With Metastatic Prostate Cancer - Schmidkonz, Christian; Cordes, Michael; Beck, Michael; Goetz, Theresa Ida; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Uder, Michael; Wullich, Bernd; Goebell, Peter; Kuwert, Torsten; Ritt, Philipp; et al. (Clinical Nuclear Medicine, 2018)
BACKGROUND: We investigated the role of Tc-MIP-1404 (Progenics Pharmaceuticals, Inc, New York, NY) SPECT/CT of PSMA expression in the assessment of treatment response in patients with metastatic prostate cancer. METHODS: We retrospectively analyzed Tc-MIP-1404 SPECT/CT scans from 28 patients with metastatic prostate cancer examined before initiation and after completion of therapy. Eight of these patients had been treated with androgen deprivation therapy, 10 with docetaxel, and another 10 with external beam radiotherapy. On the CT images from SPECT/CT, treatment response was assessed according to RECIST 1.1 criteria; independently from that analysis, maximal standardized uptake values (SUVmax) were quantified in representative tumor lesions and treatment response assumed at differences in SUVmax greater than 30%. Radiographic response assessment was correlated to biochemical response (BR) based on prostate-specific antigen serum levels. RESULTS: The concordance rate between SPECT and BR was 75% (95% confidence interval [CI], 0.55-0.89) (Cohen κ = 0.57; 95% CI, 0.29-0.85; P ≤ 0.01), higher than for that between SPECT and CT with 57% (95% CI, 0.37-0.76) (κ = 0.40; 95% CI, 0.14-0.65; P ≤ 0.01), as well as that between CT and BR with 50% (95% CI, 0.31-0.69) (κ = 0.31; 95% CI, 0.06-0.57, P ≤ 0.05). Discordant findings between SPECT and CT were most likely due to limitations of CT in assessing metastases in lymph nodes, as well as bone involvement, which was sometimes not detectable on CT scans. CONCLUSIONS: The high agreement between treatment response, as assessed by Tc-MIP-1404 SPECT/CT and BR, suggests a possible role of that imaging tool for monitoring treatment in metastatic prostate cancer. Larger, ideally prospective trials are needed to help to reveal the full potential of SPECT imaging of PSMA expression in that regard.
EVALuna2:34693

Bedeutung der parametrischen und molekularen Bildgebung für das therapeutische Management des Mammakarzinoms - Hack, Carolin; Wetzl, Matthias; Schmidt, Daniela; Beckmann, Matthias (Die Radiologie, 2024)
Background: In recent years, various magnetic resonance (MRI) and positron emission tomography (PET) parameters have been investigated in breast cancer. Parametric imaging focuses on the visualization and quantification of biological, physiological, and pathological processes at the cellular and molecular level. It therefore provides important insights into the key processes in carcinogenesis and tumor progression. This article aims to illustrate the importance for the management of breast cancer. Materials and methods: Based on the current literature, an overview of the current state of parametric breast imaging and its importance in therapy management is given. Moreover, future opportunities and challenges are highlighted. Results: Parametric imaging in breast cancer includes MRI, nuclear medicine procedures such as PET, the combination of different techniques (PET-CT, PET-MRI) and the use of specific radiotracers. Parametric MRI of the breast mainly uses T2 and diffusion-weighted imaging (DWI) as well as dynamic contrast-enhanced MRI (CM-MRI). Quantitative and qualitative imaging biomarkers provide insights into tumor biology and allow conclusions to be drawn about the molecular subtype or prognosis. Conclusions: Recently, parametric imaging has become established in breast diagnostics. It is constantly evolving and will continue to gain in importance in the forthcoming years. It offers the opportunity to improve the diagnosis and treatment management of breast cancer.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Breast neoplasms; Gene expression; Magnetic resonance imaging; Positron emission tomography; Preoperative diagnostics

Beta-HCG elevation as first sign of a malignant somatic transformation of a non-seminomatous germ cell tumor - Peuser, Moritz; Hartmann, Arndt; Schmidt, Daniela; Mackensen, Andreas; Meidenbauer, Norbert (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Classification of three prognostically different groups of head and neck cancer patients based on their metabolic response to induction chemotherapy (IC-1) - Semrau, Sabine; Schmidt, Daniela; Hecht, Markus; Haderlein, Marlen; Kitzsteiner, Christian; Müller, Susanna; Traxdorf, Maximilian; Agaimy, Abbas; Iro, Heinrich; Kuwert, Torsten; Fietkau, Rainer (Oral Oncology, 2020)
Objectives: There exist no uniform decision criteria for conservative organ preservation treatments in head and neck cancer patients. Even with 18F-FDG-PET/CT after induction chemotherapy patient selection is challenging. This study correlated metabolic tumor response with treatment types and recurrence patterns. Materials and methods: Decrease in SUVmax in 18F-FDG-PET/CT was measured 21–28 days after IC-1 in 102 patients and correlated to cancer-specific endpoints. Results: Residual SUVmax (resSUVmax) values were uniformly distributed across five cut-off levels (0–0.2 vs. >0.2–0.4 vs. >0.4–0.6 vs. >0.6–0.8 vs. >0.8) containing 20%, 25% 25%, 15% and 15% of patients. Patients were stratified into three response categories according to residual SUVmax (Group A: 0–0.4 = high response Group B: >0.4–0.8 = moderate response, Group C > 0.8 = non-response), 5-year local control rates were 90.5% (Group A) vs. 78.9% (Group B; univariate p = 0.07, multivariate: HR: 3.6, p = 0.03) vs. 49.4% (Group C vs. B; univariate p = 0.04, multivariate: HR 5.5, p < 0.01). After IC-1, Group A received chemoradiotherapy (CRT) only. Group B received surgery plus either (chemo)radiotherapy (B_S + RT/CRT) or chemoradiotherapy (B_CRT), yielding local control rates of 100% and 74.2% (p = 0.11). Group C received surgery plus CRT or CRT alone; both achieved equally poor local control (p = 0.71). Group C had significantly worse distant metastasis-free survival and overall survival than Groups A and B (p < 0.05). Conclusion: Metabolic response after IC-1 differentiates HNC patients into three subgroups predicting local tumor control. Non-response was associated with a poor outcome.
CRIS-Team Scopus Importer:2019-12-03
Keywords: 18F-FDG PET/CT; Chemoradiation; Chemoselection; Head and neck cancer; Hypopharynx; Induction chemotherapy; Larynx; Metabolic response; Resection

Comparison of lesion detection and quantitation of tracer uptake between PET from a simultaneously acquiring whole-body PET/MR hybrid scanner and PET from PET/CT - Wiesmüller, Marco; Quick, Harald H.; Navalpakkam, Bharath; Lell, Michael; Uder, Michael; Ritt, Philipp; Schmidt, Daniela; Beck, Michael; Kuwert, Torsten; von Gall, Carl (European Journal of Nuclear Medicine and Molecular Imaging, 2013)
Purpose PET/MR hybrid scanners have recently been introduced, but not yet validated. The aim of this study was to compare the PET components of a PET/CT hybrid system and of a simultaneous whole-body PET/MR hybrid system with regard to reproducibility of lesion detection and quantitation of tracer uptake. Methods A total of 46 patients underwent a whole-body PET/CT scan 1 h after injection and an average of 88 min later a second scan using a hybrid PET/MR system. The radioactive tracers used were 18F-deoxyglucose (FDG), 18F-ethylcholine (FEC) and 68Ga-DOTATATE (Ga-DOTATATE). The PET images from PET/CT (PETCT) and from PET/MR (PETMR) were analysed for tracer-positive lesions. Regional tracer uptake in these foci was quantified using volumes of interest, and maximal and average standardized uptake values (SUVmax and SUVavg, respectively) were calculated. Results Of the 46 patients, 43 were eligible for comparison and statistical analysis. All lesions except one identified by PETCT were identified by PETMR (99.2 %). In 38 patients (88.4 %), the same number of foci were identified by PETCT and by PETMR. In four patients, more lesions were identified by PETMR than by PETCT, in one patient PETCT revealed an additional focus compared to PETMR. The mean SUVmax and SUVavg of all lesions determined by PETMR were by 21 % and 11 % lower, respectively, than the values determined by PETCT (p < 0.05), and a strong correlation between these variables was identified (Spearman rho 0.835; p < 0.01). Conclusion PET/MR showed equivalent performance in terms of qualitative lesion detection to PET/CT. The differences demonstrated in quantitation of tracer uptake between PETCT and PETMR were minor, but statistically significant. Nevertheless, a more detailed study of the quantitative accuracy of PETMR and the factors governing it is needed to ultimately assess its accuracy in measuring tissue tracer concentrations.

Computer-aided evaluation of the anatomical accuracy of hybrid SPECT/spiral-CT imaging of lesions localized in the neck and upper abdomen - Hahn, Dieter; Bennewitz, Christian; Kuwert, Torsten; Han, Jingfeng; Ritt, Philipp; Hahn, Dieter; Thimister, Willie; Hornegger, Joachim; Uder, Michael; Schmidt, Daniela (Nuclear Medicine Communications, 2012)
OBJECTIVE: The purpose of this study was to investigate the anatomical accuracy of hardware-based single-photon emission computed tomography/computed tomography (SPECT/CT) registration in the upper abdomen and neck. METHODS: The database consisted of 90 patients referred for SPECT/CT for diagnostic workup of either thyroid/parathyroid disease (n=46) or abdominal neuroendocrine tumours (n=44). In the first group, Tc-MIBI was used as the tracer and in the second I-metaiodobenzylguanidine (n=13), In-octreotide (n=28) or Tc-octreotide (n=3). For predefined structures represented by both modalities, the distances between the centres of gravity of their CT and SPECT representation were determined in a semiautomated manner. In cervical data sets, this analysis was performed for the submandibular salivary glands (n=92) and in abdominal data sets for 69 neoplastic foci. RESULTS: The mean distances were 5.7±2.0 mm (range: 1.84-9.67 mm) in the neck and 6.8±3.3 mm (range: 1.4-19.7 mm) in the abdomen. In 42 out of 92 of the cervical and 40 out of 69 of the abdominal data sets at least one of the X-direction-determined, Y-direction-determined, and Z-direction-determined distances was greater than the SPECT pixel width of 4.6 mm. CONCLUSION: The anatomical accuracy of hardware-based SPECT/CT fusion depends also on the region of the body studied. For example, in the neck and upper abdomen the accuracy is lower than in the lower lumbar spine. In clinical routine, SPECT/CT data sets acquired for the neck and upper abdomen should be regularly checked and corrected for SPECT/CT misalignment. This is, in particular, important when CT-based corrections of SPECT involving pixelwise data integration such as for attenuation correction are made. © 2012 Wolters Kluwer Health | Lippincott Williams & Wilkins.

Hybrid Molecular Imaging in Differentiated Thyroid Carcinoma - Schmidt, Daniela; Kuwert, Torsten (Frontiers of Hormone Research, 2016)
Radioactive isotopes of radioiodine are frequently used in differentiated thyroid carcinoma (DTC) both for diagnosis and therapy. Their accumulation in thyroid cancer tissue is dependent on the expression and activity of the sodium-iodide symporter (NIS). Scintigraphic imaging using either planar or single-photon emission computed tomography (SPECT) cameras allows the visualization of their distribution within the human body. Due to only a poor visualization of morphology by these techniques, their diagnostic accuracy is, however, limited. This limitation is overcome when hybrid systems integrating a SPECT camera with an X-ray CT scanner are used. Roughly one third of patients with diagnostically unclear foci of radioiodine accumulation will benefit from the use of SPECT/CT, also in terms of therapeutic management. SPECT/CT has, therefore, become the gold standard of nuclear imaging in DTC. NIS expression may be absent in DTC. In this case, the glucose transporters are usually upregulated. Therefore, PET/CT using 18F-deoxyglucose can be used to diagnose and localize tumor recurrence as a prerequisite to, in particular, surgical intervention.
EVALuna2:13862

Individual Calculation of Effective Dose and Risk of Malignancy Based on Monte Carlo Simulations after Whole Body Computed Tomography - Kopp, Markus; Loewe, Tobias; Wüst, Wolfgang; Brand, Michael; Wetzl, Matthias; Nitsch, Wolfram; Schmidt, Daniela; Beck, Michael; Schmidt, Bernhard; Uder, Michael; May, Matthias (Scientific Reports, 2020)
Detailed knowledge about radiation exposure is crucial for radiology professionals. The conventional calculation of effective dose (ED) for computed tomography (CT) is based on dose length product (DLP) and population-based conversion factors (k). This is often imprecise and unable to consider individual patient characteristics. We sought to provide more precise and individual radiation exposure calculation using image based Monte Carlo simulations (MC) in a heterogeneous patient collective and to compare it to phantom based MC provided from the National Cancer Institute (NCI) as academic reference. Dose distributions were simulated for 22 patients after whole-body CT during Positron Emission Tomography-CT. Based on MC we calculated individual Lifetime Attributable Risk (LAR) and Excess Relative Risk (ERR) of cancer mortality. EDMC was compared to EDDLP and EDNCI. EDDLP (13.2 ± 4.5 mSv) was higher compared to EDNCI (9.8 ± 2.1 mSv) and EDMC (11.6 ± 1.5 mSv). Relative individual differences were up to −48% for EDMC and −44% for EDNCI compared to EDDLP. Matching pair analysis illustrates that young age and gender are affecting LAR and ERR significantly. Because of these uncertainties in radiation dose assessment automated individual dose and risk estimation would be desirable for dose monitoring in the future.
CRIS-Team Scopus Importer:2020-06-23

Long-term control with chemoradiation of initially metastatic mixed adenoneuroendocrine carcinoma of the rectum: A case report - Semrau, S.; Agaimy, Abbas; Pavel, Marianne Ellen; Lubgan, Dorota; Schmidt, Daniela; Golcher, H.; Grützmann, Robert; Fietkau, Rainer; Cavallaro, Alexander Josef (Journal of Medical Case Reports, 2019)
Background: Mixed adenoneuroendocrine carcinomas are highly malignant tumors with both adenocarcinomatous and neuroendocrine components. They can originate in any organ but are more common in the rectum. Due to their rarity, current treatment recommendations for mixed adenoneuroendocrine carcinoma are based on limited data and follow general guidelines for the management of adenocarcinomas and neuroendocrine neoplasms. Uncertainty regarding the efficacy of the available local and systemic treatment strategies is a compounding issue. Even those patients with locally limited disease have a relatively short life expectancy. In this report, we describe a case of deep rectal mixed adenoneuroendocrine carcinoma with long survival after chemoradiation. Case presentation: A 48-year-old Caucasian woman was diagnosed with a grade 3 rectal adenocarcinoma combined with a poorly differentiated large cell neuroendocrine carcinoma component and synchronous metastases (cT3cN1cM1) in both lobes of the liver in 2012. She received concomitant chemoradiotherapy followed by four additional cycles of cisplatin plus irinotecan. Initial treatment induced complete remission of the rectal tumor and liver metastases. Consequently, it was not necessary to surgically resect the primary tumor or any of the metastases. Three months after the end of treatment, one metastasis in the first segment of the liver showed regrowth, and stereotactic body radiotherapy of the metastasis and chemotherapy resulted in a clinical complete response. The patient has been recurrence-free for more than 5 years. Conclusions: Extended long-term control of a poorly differentiated metastatic (stage IV) mixed adenoneuroendocrine carcinoma is rare. The multimodal first- and second-line regimens of radiotherapy and chemotherapy described in this case report represent a new therapeutic approach. Encouraged by the results in this case, we compiled a review of the literature on mixed adenoneuroendocrine carcinoma.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Chemoradiation; MANEC; Rectum; SBRT

Metabolic Response of Short-term Induction Chemotherapy (IC) for Therapy Selection as well as Prediction of long-term local and systemic Therapy Success for Head and Neck cancer. The Results of 100 Patients - Semrau, S.; Haderlein, Marlen; Schmidt, Daniela; Waldfahrer, F.; Scherl, C.; Lettmaier, S.; Kuwert, Torsten; Iro, Heinrich; Fietkau, Rainer (2017)
EVALuna2:32895

Rate of elimination of radioiodine-avid lymph node metastases of differentiated thyroid carcinoma by postsurgical radioiodine ablation. A bicentric study - Ilhan, Harun; Mustafa, Mona; Bartenstein, Peter; Kuwert, Torsten; Schmidt, Daniela (Nuklearmedizin-Nuclear Medicine, 2016)
SPECT/CT detects radioiodine-positive cervical lymph node metastases (LNMs) of differentiated thyroid carcinoma (DTC) at the time of postsurgical radioablation (RA). Preliminary evidence indicates that the majority of LNMs are successfully treated by RA. The aim of this study was to confirm this evidence in a bicentric setting and to evaluate whether size is a predictor for successful elimination.Since 01/2007 and 05/2008, respectively, SPECT/spiral-CT is performed routinely in all patients with DTC at RA in two University Clinics. The outcome of iodine-positive LNMs identified by SPECT/CT until 12/2012 was analyzed by follow-up diagnostic (131)I scans and serum thyreoglobulin (Tg) values. LNM volume and short-axis diameter were evaluated as prognostic factors by a receiver-operating characteristic (ROC) analysis.79 patients with 97 iodine-positive LNMs were included. Surgery was carried out in 8 patients with 13 LNMs due to the presence of additional iodine-negative lesions. Of the remaining 84 LNMs, 74 (88%) were successfully treated as demonstrated by radioiodine scans at follow-up. 10 LNMs persisted. 67/70 LNMs smaller than 0.9 ml were treated successfully, whereas this was the case of only 6/14 exceeding this threshold. Using this cut-off level to predict treatment success, sensitivity, specificity, positive and negative predictive value were 92%, 73%, 96%, and 57%. Results for short-axis diameter (cut-off level < 1cm) were 90%, 69%, 94% and 56%.RA is effective in the treatment of the majority of (131)I-positive LNMs identified in SPECT/CT images. In this study, 88% of iodine-positive LNM in DTC were successfully treated by radioiodine given at RA. Both LNM volume and diameter are reliable predictors of treatment success.
EVALuna2:13866

Repeating of local therapy of distant metastases increases overall survival in patients with synchronous metastasized rectal cancer-a monocentric analysis - Haderlein, Marlen; Lettmaier, Sebastian; Langheinrich, Melanie; Schmid, Axel; Semrau, Sabine; Hecht, Markus; Beck, Michael; Schmidt, Daniela; Grützmann, Robert; Fietkau, Rainer; Denz, Axel (International Journal of Colorectal Disease, 2018)
PURPOSE: The aim was to evaluate the outcome of treatment-naive patients with synchronous metastatic rectal cancer after chemotherapy with FOLFOXIRI followed by local therapeutic procedures of all tumor lesions as complete as possible. METHODS: We reviewed data of 30 patients with synchronous distant metastatic rectal cancer who underwent chemotherapy with FOLFOXIRI and subsequent local therapy in our institution. RESULTS: Median follow-up was 28 months (range: 8; 74). Cumulative overall survival (OS) and progression-free survival (PFS) was 93.3, 76.9, 55.6% and 46.2, 29.7, 29.7% after 1, 2, 4 years. Non-response to chemotherapy with FOLFOXIRI was associated with a highly significant decreased OS (p < 0.0001). The consistent use of local ablative procedures led to a statistically significant increase in OS (p < 0.0001), but not in PFS (p = 0.635). Patients with ≤ 4 distant metastases showed a better OS (p = 0.033). CONCLUSIONS: Response to intensified first-line chemotherapy with FOLFOXIRI, treatment of the primary rectal tumor, and repeated thorough local ablative procedures in patients with synchronous metastasized rectal cancer may lead to long-term survival, even in a subset of patients with unresectable disease at initial diagnosis.
EVALuna2:36458

RESOLUTION OF VASCULAR INFLAMMATION IN PATIENTS WITH GIANT CELL ARTERITIS RECEIVING GLUCOCORTICOIDS, METHOTREXATE OR TOCILIZUMAB TREATMENT-DATA FROM THE ITALIAN/GERMAN RIGA STUDY - Schonau, Verena; Roth, Jessica; Tascilar, Koray; Rech, Jürgen; Schmidt, Daniela; Kuwert, Torsten; Crescentini, Filippo; Boiardi, Luigi; Casali, Massim Iliano; Versari, Annibale; Schett, Georg; Salvarani, Carlo; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12

Resolution of vascular inflammation in patients with new-onset giant cell arteritis: data from the RIGA study - Schönau, Verena; Roth, Jessica; Tascilar, Koray; Corte, Giulia; Manger, Bernhard; Rech, Jürgen; Schmidt, Daniela; Cavallaro, Alexander Josef; Uder, Michael; Crescentini, Filippo; Boiardi, Luigi; Casali, Massimiliano; et al. (Rheumatology, 2021)
OBJECTIVES: Efficacy evaluation of GCA treatment is primarily based on non-specific symptoms and laboratory markers. We aimed to assess the change in vascular inflammation in patients with large vessel (LV)-GCA under different treatments using [18F]FDG PET/CT. METHODS: Observational study on patients with new-onset, active LV-GCA starting treatment with either prednisolone monotherapy (PRED) or combination with MTX or tocilizumab (TOC). All patients underwent baseline and follow-up PET/CT. The aorta and its major branches were assessed using PET vascular activity score (PETVAS) by independent readers. Cumulative glucocorticoid doses and cessation of glucocorticoid treatment were documented in all patients. RESULTS: We included 88 LV-GCA patients, 27 were treated with PRED, 42 with MTX and 19 with TOC. PETVAS decreased from 18.9-8.0 units at follow-up in the overall population (P <0.001). PETVAS changes were numerically higher in patients receiving MTX (-12.3 units) or TOC (-11.7 units) compared with PRED (-8.7). Mean cumulative prednisolone dosages were 5637, 4418 and 2984 mg in patients treated with PRED, MTX and TOC (P =0.002). Risk ratios for glucocorticoid discontinuation at the time of follow-up PET/CT were 6.77 (95% CI: 1.01, 45.29; P =0.049) and 16.25 (95% CI: 2.60, 101.73; P =0.003) for MTX and TOC users compared with PRED users. CONCLUSION: Treatment of LV-GCA inhibits vascular inflammation in the aorta and its major branches. While similar control of vascular inflammation was achieved with PRED, MTX and TOC treatments, TOC showed a strong glucocorticoid sparing effect, supporting the concept of initial combination therapy.
CRIS-Team Scopus Importer:2021-09-24
Keywords: 18F-fluorodeoxyglucose positron emission tomography/computed tomography; giant cell arteritis; glucocorticoids; large vessel vasculitis; methotrexate; tocilizumab; treatment

Single-cycle induction chemotherapy before chemoradiotherapy or surgery in functionally inoperable head and neck squamous cell carcinoma: 10-year results - Breheret, Marius; Lubgan, Dorota; Haderlein, Marlen; Hecht, Markus; Traxdorf, Maximilian; Schmidt, Daniela; Müller, Sarina Katrin; Kitzsteiner, Christian; Kuwert, Torsten; Iro, Heinrich; Fietkau, Rainer; Semrau, Sabine (European Archives of Oto-Rhino-Laryngology, 2019)
Introduction The response to induction chemotherapy (IC) predicts local control after conservative treatment of laryngeal, meso- and hypopharyngeal head and neck squamous cell carcinoma (HNSCC) and can thus help to avoid surgery. Single-cycle induction chemotherapy may help to maintain a low local recurrence rate while keeping the overall toxicity manageable. However, long-term data on single-cycle IC response by tumor location is lacking. Methods N = 102 patients with functionally inoperable primary HNSCC of the larynx (n = 43), hypopharynx (n = 42) or mesopharynx/tongue (n = 17) received one cycle of docetaxel (75 mg/m(2), d1) plus cisplatin (30 mg/m(2), d1-3) or carboplatin (AUC 1.5, d1-3) and a response evaluation 3 weeks later. Responders (>= 30% tumor size reduction and >= 20% SUVmax decrease in F-18-FDG PET/CT) were recommended chemoradiotherapy (CRT), and non-responders surgery. Results The overall response rate was 72.5%. All 74 responders and 10 non-responders received primary CRT, and 18 patients received primary surgery after single-cycle IC. Overall 10-year local recurrence-free survival (LRFS) was 73.7%. Three-year LRFS was 88.2% (mesopharynx/tongue), 88.2% (larynx), and 73.3% (hypopharynx); p = 0.17. 3-year distant metastasis-free survival (DMFS) was 94.1% (mesopharynx/tongue), 88.0% (larynx) and 76.4% (hypopharynx); p > 0.05. This influenced the 3-year cancer-specific survival (CSS) for larynx (91.2%) vs. hypopharynx tumors (60.8%); p = 0.003, but CSS was not different to tumors in the mesopharynx/tongue (81.4%); p > 0.05. Conclusions A single-cycle induction chemotherapy for HNSCC enables surgery plus adjuvant therapy as well as chemoradiotherapy. The long-term local and distant disease control was good but varied between tumors in the larynx and mesopharynx/tongue vs. hypopharynx.
CRIS-Team WoS Importer:2019-10-18

Single-cycle induction chemotherapy followed by chemoradiotherapy or surgery in patients with head and neck cancer: What are the best predictors of remission and prognosis? - Semrau, Sabine; Haderlein, Marlen; Schmidt, Daniela; Lell, Michael; Wolf, Walburga; Waldfahrer, Frank; Uder, Michael; Iro, Heinrich; Kuwert, Torsten; Fietkau, Rainer (Cancer, 2015)
There is controversy over the concept of function and organ preservation by chemotherapy/chemoradiation instead of surgery in locally advanced cancer of the larynx or pharynx. Tumor response to induction chemotherapy (ICT) can help in choosing between conservative and surgical treatment. This study compared 3 methods of assessing response to ICT: endoscopy, computed tomography, and (18) F-FDG-PET/CT.Primary response to 1 cycle of ICT with docetaxel plus platinum was assessed by the aforementioned methods in 62 laryngopharyngeal cancer patients. Endoscopic response was the deciding factor for selecting further treatment: surgery for endoscopic nonresponders (<30% tumor response) versus chemoradiotherapy for endoscopic responders.ICT achieved endoscopic response in 48 of 62 patients (77%). Individual relative residual tumor activity of standardized uptake value (resSUVmax ) in (18) F-FDG-PET/CT was a median 0.38 of baseline (0.09-1.71), whereas residual tumor extent in CT (resCT) was 0.75 of baseline (0.32-1.20). Endoscopic responders and nonresponders differed significantly in SUVmax after ICT (postSUVmax , 6.0 vs 14.5; P < .001), resSUVmax (0.34 vs 0.81, P < .001), and resCT (0.71 vs 0.87, P = .004), but not in maximum tumor diameter after ICT (14 vs 20 mm, P = .11). resSUVmax <0.8 and absolute postSUVmax <10 provided the best discriminatory power for long-term success criteria (tumor-free survival, overall survival).Metabolic tumor response showed very good correlation with clinical tumor response to ICT. The value of metabolic response detected by (18) F-FDG-PET/CT should be explored in a prospective clinical trial. Cancer 2015;121:1214-1222. © 2014 American Cancer Society.
EVALuna2:13821

SPECT/CT With the PSMA Ligand 99mTc-MIP-1404 for Whole-Body Primary Staging of Patients With Prostate Cancer - Schmidkonz, Christian; Cordes, Michael; Beck, Michael; Goetz, Theresa Ida; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Uder, Michael; Wullich, Bernd; Goebell, Peter; Kuwert, Torsten; Ritt, Philipp (Clinical Nuclear Medicine, 2018)
BACKGROUND: Tc-MIP-1404 (Progenics Pharmaceuticals, Inc, New York, NY) is a novel ligand binding to prostate-specific membrane antigen suitable for SPECT. There are, as yet, no data concerning its use in whole-body primary staging and its interobserver variability in patients with prostate cancer (PC) prior to therapy. METHODS: A search of our clinical database from April 2013 to May 2017 yielded 93 patients with histologically confirmed cancer in whom Tc-MIP-1404 SPECT/CT had been performed for primary whole-body staging before therapy. Whole-body planar and SPECT/CT images of the lower abdomen and thorax had been obtained 3 to 4 hours postinjection of 706 ± 72 MBq Tc-MIP-1404. Images were visually analyzed for extent and location of abnormal uptake by 2 experienced nuclear physicians. Interobserver agreement for detection of primary tumor and metastatic lesions was assessed. In addition, SUVs of prostate-specific membrane antigen-positive regions of the prostate were determined in all patients, and from these, a variable reflecting total tumor load in the prostate gland was calculated (TUprostate). Follow-up reports of subsequent therapeutic interventions were available in 52 (56%) of all patients with a median follow-up of 18 months. RESULTS: In 90 (97%) of 93 patients, prostate uptake above background was detected as correlate of the histologically diagnosed PC. Forty-eight lymph node and 29 bone metastases were detected in 16 and 9 patients, respectively. In addition, 3 patients had disseminated bone metastases. No distant organ metastases were found. Interobserver agreement was high for the overall scan result (97%), as well as for the detection of the primary tumor (97%), of lymph node metastases (97%), and of bone metastases (99%). Recurrence of PC occurred in 5 patients in whom follow-up was available (10%). TUprostate was significantly higher in patients with Gleason scores of 8 or greater compared with patients with Gleason scores of 7 or less and at prostate-specific antigen (PSA) serum levels of 10 ng/mL or greater compared with PSA serum levels of 10 ng/mL or less. TUprostate of greater than 26 in the primary tumor predicted the occurrence of lymph node or bone metastases with a sensitivity of 82% and specificity of 76%. CONCLUSIONS: MIP-1404 SPECT/CT has a high accuracy and low interobserver variability in the diagnosis of PC and allows detection of lymph node and bone metastases in a significant proportion of as yet untreated PC patients. TUprostate is correlated with Gleason score and PSA serum concentration and allows prediction of the occurrence of lymph node and bone metastases with moderate accuracy at primary staging.
EVALuna2:32786

Successful targeting of BRAF V600E mutation with vemurafenib in a treatment-resistant extragonadal non-seminomatous germ cell tumor - Meintker, Lisa; Haller, Florian; Tögel, Lars; Schmidt, Daniela; Waibel, Heidi; Mackensen, Andreas; Meidenbauer, Norbert (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Successful Targeting of BRAF V600E Mutation With Vemurafenib in a Treatment-Resistant Extragonadal Nonseminomatous Germ-Cell Tumor - Meintker, Lisa; Haller, Florian; Tögel, Lars; Schmidt, Daniela; Waibel, Heidi; Hartmann, Arndt; Mackensen, Andreas; Meidenbauer, Norbert (JCO Precision Oncology, 2020)

The Distribution of Pelvic Nodal Metastases in Prostate Cancer Reveals Potential to Advance and Personalize Pelvic Radiotherapy - Filimonova, Irina; Schmidt, Daniela; Mansoorian, Sina; Weissmann, Thomas; Siavooshhaghighi, Hadi; Kuwert, Torsten; Bert, Christoph; Frey, Benjamin; Distel, Luitpold; Lettmaier, Sebastian; Fietkau, Rainer; Putz, Florian; et al. (Frontiers in Oncology, 2021)
Background: Traditional clinical target volume (CTV) definition for pelvic radiotherapy in prostate cancer consists of large volumes being treated with homogeneous doses without fully utilizing information on the probability of microscopic involvement to guide target volume design and prescription dose distribution. Methods: We analyzed patterns of nodal involvement in 75 patients that received RT for pelvic and paraaortic lymph node metastases (LNs) from prostate cancer in regard to the new NRG-CTV recommendation. Non-rigid registration-based LN mapping and weighted three-dimensional kernel density estimation were used to visualize the average probability distribution for nodal metastases. As independent approach, the mean relative proportion of LNs observed for each level was determined manually and NRG and non-NRG levels were evaluated for frequency of involvement. Computer-automated distance measurements were used to compare LN distances in individual patients to the spatial proximity of nodal metastases at a cohort level. Results: 34.7% of patients had pelvic LNs outside NRG-consensus, of which perirectal was most common (25.3% of all patients) followed by left common iliac nodes near the left psoas major (6.7%). A substantial portion of patients (13.3%) had nodes at the posterior edge of the NRG obturator level. Observer-independent mapping consistently visualized high-probability hotspots outside NRG-consensus in the perirectal and left common iliac regions. Affected nodes in individual patients occurred in highly significantly closer proximity than at cohort-level (mean distance, 6.6 cm vs. 8.7 cm, p < 0.001). Conclusions: Based on this analysis, the common iliac level should extend to the left psoas major and obturator levels should extend posteriorly 5 mm beyond the obturator internus. Incomplete coverage by the NRG-consensus was mostly because of perirectal involvement. We introduce three-dimensional kernel density estimation after non-rigid registration-based mapping for the analysis of recurrence data in radiotherapy. This technique provides an estimate of the underlying probability distribution of nodal involvement and may help in addressing institution- or subgroup-specific differences. Nodal metastases in individual patients occurred in highly significantly closer proximity than at a cohort-level, which supports that personalized target volumes could be reduced in size compared to a “one-size-fits-all” approach and is an important basis for further investigation into individualized field designs.
CRIS-Team Scopus Importer:2021-02-05
Keywords: lymph node metastases; mapping; patterns of recurrence; pelvic radiotherapy; prostate cancer

Therapies for synchronous malignomas - the importance of interdisciplinary oncology - Müller, Sarina Katrin; Haderlein, Marlen; Traxdorf, Maximilian; Semrau, Sabine; Agaimy, Abbas; Lettmaier, Sebastian; Gostian, Antoniu-Oreste; Schubart, Christoph; Mantsopoulos, Konstantinos; Schmidt, Daniela; Wiesmüller, Marco; Sievert, Matti; et al. (Laryngo-Rhino-Otologie, 2021)
CRIS-Team WoS Importer:2021-08-06

The value of (18)F-FDG-PET/CT in identifying the cause of fever of unknown origin (FUO) and inflammation of unknown origin (IUO): data from a prospective study - Schoenau, Verena; Vogel, Kristin; Englbrecht, Matthias; Wacker, Jochen; Schmidt, Daniela; Manger, Bernhard; Kuwert, Torsten; Schett, Georg (Annals of the Rheumatic Diseases, 2017)
Fever of unknown origin (FUO) and inflammation of unknown origin (IUO) are diagnostically challenging conditions. Diagnosis of underlying disease may be improved by (18)F-fluorodesoxyglucose positron emission tomography ((18)F-FDG-PET).Prospective study to test diagnostic utility of (18)F-FDG-PET/CT in a large cohort of patients with FUO or IUO and to define parameters that increase the likelihood of diagnostic (18)F-FDG-PET/CT. Patients with FUO or IUO received (18)F-FDG-PET/CT scanning in addition to standard diagnostic work-up. (18)F-FDG-PET/CT results were classified as helpful or non-helpful in establishing final diagnosis. Binary logistic regression was used to identify clinical parameters associated with a diagnostic (18)F-FDG-PET/CT.240 patients were enrolled, 72 with FUO, 142 with IUO and 26 had FUO or IUO previously (exFUO/IUO). Diagnosis was established in 190 patients (79.2%). The leading diagnoses were adult-onset Still's disease (15.3%) in the FUO group, large vessel vasculitis (21.1%) and polymyalgia rheumatica (18.3%) in the IUO group and IgG4-related disease (15.4%) in the exFUO/IUO group. In 136 patients (56.7% of all patients and 71.6% of patients with a diagnosis), (18)F-FDG-PET/CT was positive and helpful in finding the diagnosis. Predictive markers for a diagnostic (18)F-FDG-PET/CT were age over 50 years (p=0.019), C-reactive protein (CRP) level over 30 mg/L (p=0.002) and absence of fever (p=0.001).(18)F-FDG-PET/CT scanning is helpful in ascertaining the correct diagnosis in more than 50% of the cases presenting with FUO and IUO. Absence of intermittent fever, higher age and elevated CRP level increase the likelihood for a diagnostic (18)F-FDG-PET/CT.
EVALuna2:13447

Thrombopoietin receptor agonists for acquired thrombocytopenia following anti-CD19 CAR-T-cell therapy: A case report - Jitschin, Regina; Kharboutli, Soraya; Stoll, Andrej; Büttner-Herold, Maike; Schmidt, Daniela; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon; Baur, Rebecca (Journal for ImmunoTherapy of Cancer, 2021)
Chimeric antigen receptor (CAR)-modified T-cells targeting CD19 represent a promising therapy for relapsed or refractory (r/r) lymphoma and leukemia. The most common adverse events are immune related and include cytokine release syndrome and neurotoxicity. However, early and late hematological toxicity has emerged as a substantial clinical hurdle leading among others to an increased risk for infections or bleeding. The underlying pathophysiology remains elusive and supportive measures comprise stem cell support or the use of growth factors. Here, we report a 66-year-old woman with r/r diffuse large B-cell lymphoma that received anti-CD19 CAR-T-cells achieving a complete metabolic remission. At month 3 after adoptive cell transfer, the patient still exhibited a grade 3 anemia and a grade 4 thrombocytopenia. The latter required regular platelet transfusions. Bone marrow smear revealed hypocellularity without dysplasia. Despite reduced megakaryopoiesis, immature platelet fraction was elevated indicating an at least partially consumptive underlying component. Based on the successful use of Romiplostim, a thrombopoietin receptor-agonist, in aplastic anemia and immune thrombocytopenia, we treated our patient accordingly. Platelet count (and hemoglobin levels) increased and the patient remains transfusion-free. Taken together, our therapeutic approach could represent a novel strategy for managing CAR-T-cell-related hematotoxicity but, self-evidently, requires further controlled clinical studies.
CRIS-Team Scopus Importer:2021-07-30
Keywords: adoptive; chimeric antigen; hematologic neoplasms; immunotherapy; receptors

Ultrasound of Thyroid Nodules Ultrasound Characteristics and Risk of Carcinoma - Schmidt, Daniela (Laryngo-Rhino-Otologie, 2019)
Thyroid ultrasound is used as a first-line diagnostic procedure to evaluate thyroid nodules. Several ultrasound characteristics have been associated with an increased risk of malignancy. Based on these criteria, classification systems are being developed to categorize thyroid nodules and stratify their malignant risk to decide about further evaluation. Up to now only morphological features are taken into account. The results of Doppler ultrasonography have not yet been included in these thyroid imaging and reporting systems (TI-RADS) although predominantly internal flow is associated with malignancy of thyroid follicular neoplasia. Currently, the new systems will be evaluated and may be optimized for clinical practice. Furthermore there are first attempts to standardize the reporting of ultrasound features of thyroid nodules to enhance patient care by optimizing the diagnostic capabilities of an ultrasound examination.
CRIS-Team WoS Importer:2019-03-06

VEXAS syndrome mimicking lupus-like disease - Valor-Mendez, Larissa; Sticherling, Michael; Zeschick, Martin; Atreya, Raja; Schmidt, Daniela; Waldfahrer, Frank; Saake, Marc; Hüffmeier, Ulrike; Schett, Georg; Rech, Jürgen (Rheumatology, 2023)
CRIS-Team WoS Importer:2023-03-17